The Impact of Social Trust, Social Network and Financial Innovation on the Financial Well-Being of Micro-Entrepreneurs in Malaysia: A Pilot Study - Mohd Hidzir, Putri Aliah; Ismail, Shafinar; Syed Nor, Sharifah Heryati; Md Sahiq, Aqilah Nadiah (Information Management and Business Review, 2024)
This study aims to assess the reliability and validity of a questionnaire designed to measure the impact of social trust, social networks, and financial innovation on the financial well-being of micro-entrepreneurs in Malaysia. Employing a descriptive research design and a cross-sectional approach, data were collected from 140 micro-entrepreneurs, with the questionnaire serving as the primary research instrument. The findings reveal strong internal consistency within the factors under investigation, underscoring the robustness of the questionnaire. Additionally, insights into the demographic profile of micro-entrepreneurs offer a valuable understanding of their characteristics and operational dynamics. The implications of this study extend to policymakers, industry stakeholders, and researchers, providing actionable insights to support the sustainability and resilience of micro-entrepreneurs. Overall, this research contributes to advancing knowledge in the areas of social trust, social networks, and financial innovation concerning the financial well-being of micro-enterprises. It holds significant implications for fostering economic growth, reducing inequalities, and promoting inclusive development in Malaysia.